Evaluation of predictors of quality for use in early generation selection - Clarke J.M.; Clarke F.R.; McCaig T.N.; Knox R.E.; Ames N.P. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Grain protein concentration, protein quality, and colour are major quality attributes of durum wheat. Breeders and their cereal chemist colleagues use predictors of these end-use quality factors in the early generations to develop improved cultivars. Techniques used in selection must be strongly correlated with semolina or pasta quality, effective in producing genetic gains through selection, and cost-efficient. Protein concentration is relatively simple to measure with Near Infrared Reflectance or other instruments, but low heritability is a problem due to the strong influence of environment. Use of appropriate experimental designs and statistical analyses can improve heritability. Rapid tests for gluten strength, such as SDS-sedimentation volume and gluten index, provide moderately heritable predictions of gluten strength and are correlated with more time-consuming rheological tests performed on semolina.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)